Full-length merozoite surface protein 1 formulated with GLA-SE adjuvant in malaria pre-exposed adults: a randomised, controlled, double-blind, parallel-group, single-centre Phase Ib trial - Kahatano, Aina-ekisha; Mpina, Maxmillian Gideon; Vanobberghen, Fiona; Hassan, Omary; Urasa, Nsiande; Sasamalo, Ibrahim; Mswata, Sarah; Paris, Daniel; Gajewski, Suzanne; Saxena, Meera; Fürle, Kristin; Kiehl, Viktoria; et al. (EClinicalMedicine, 2025)
Background - A highly effective blood-stage malaria vaccine targeting the merozoite surface protein 1 (MSP1) of Plasmodium falciparum (Pf) might complement the imperfect protection conferred by the currently available first-generation pre-erythrocytic malaria vaccines RTS,S/AS01E and R21/Matrix-M. We investigated for the first time the safety, reactogenicity and immunogenicity of full-length recombinant PfMSP1 (MSP1FL) formulated in Glucopyranosyl Lipid Adjuvant-Stable Emulsion (GLA-SE) adjuvant as a malaria vaccine in a malaria pre-exposed adult population. - Methods - We conducted a randomized, controlled, double-blind, parallel-group, single-centre Phase Ib trial in healthy participants living in a malaria-endemic setting. The trial was conducted in Bagamoyo, Tanzania between August 2023 and April 2024 and was the first study of this vaccine formulation in malaria pre-exposed participants. Forty participants were enrolled into two groups (n = 20). Eligible males and females aged 18-45 years were randomised (1:1) to receive 3 monthly doses of either the SUM-101 malaria vaccine (150 μg MSP1 FL derived from the 3D7 Pf strain formulated in 5 μg of adjuvant GLA-SE) or the Verorab rabies vaccine (control) given intramuscularly at days 0, 28 and 56. Participants were monitored for solicited adverse events up to day 7 and unsolicited adverse events up to day 28 post-vaccination through clinical observation and laboratory assessments, including haematology and blood biochemistry. The primary safety and reactogenicity outcomes were (i) local and systemic solicited adverse events (AEs) at least possibly related to SUM-101 or Verorab over 7 days after each vaccination, (ii) local and systemic unsolicited reactogenicity over 28 days after each vaccination, (iii) any severe adverse event (SAE) occurring after the first vaccination until the participant's last visit, (iv) changes in clinical laboratory safety parameters from baseline (day 0) and up to 28 days post-vaccination, and (v) changes in clinical laboratory safety parameters from pre-vaccination time points (day 0, day 28 and day 56) to 28 days following each respective dose. The primary immunogenicity outcome was the magnitude and persistence of the vaccine-induced IgM and IgG responses to SUM-101, measured by ELISA as fold-change relative to the baseline. Immunogenicity was assessed by measuring longevity and fold changes (versus baseline) of MSP1-specific IgG and IgM antibody responses, IgG subclass distribution, and Fc-receptor mediated effector functions. All participants were followed for 140 days after first dose. The trial is registered on ClinicalTrials.gov under NCT05644067. - Findings - Out of the 40 enrolled participants, 37 (93%) completed all vaccinations and follow-up procedures. Within 7 days post-vaccination, 52 solicited adverse events were reported that were at least possibly related to the Investigational Medicinal Product (IMP): 26 events occurred in 10 participants (50%) in the SUM-101 arm, and 26 events occurred in 13 participants (65%) in the Verorab arm. The majority of the solicited adverse events were mild to moderate in severity, including injection site pain, headache, and fatigue. No severe solicited adverse events, serious adverse events (SAEs), or unsolicited vaccine-related adverse events were reported. SUM-101 elicited robust MSP1-specific IgM and IgG antibody titers, with peak levels observed on day 56 and day 84, respectively. IgM antibody titers increased following each dose, peaking on day 56 with a median fold-change from baseline of 2.65 (Inter-Quartile Range (IQR): 0.80-5.10), and gradually declined after day 84 but remained elevated through day 140. IgG titers rose progressively, peaking on day 84 with a median fold-change of 20.77 (IQR: 2.60-45.29), and remained above baseline on day 140 (median 10.77, IQR: 1.98-27.07). All IgG subclasses (IgG1, IgG2, IgG3, and IgG4) exhibited increased titers. The median (IQR) IgG titers at baseline were 504 (143-1055) and 413 (239-2310) AU in the Verorab and SUM-101 groups, respectively, and the corresponding values for IgM titers were 61 (34-128) and 57 (26-95) AU. On day 84, MSP1-specific antibodies mediated Fc-receptor-dependent phagocytosis, respiratory burst, natural killer cell, and complement system activation at their highest levels compared to baseline. SUM-101 induced strain-transcending antibodies binding merozoites from Pf3D7 and PfFCB1 strains. Participants with higher pre-vaccination MSP1-specific IgG levels reached peak responses after two vaccinations, indicating that SUM-101 boosts pre-existing, naturally acquired malaria immunity. In the Verorab arm, the median values of the MSP1-specific IgG and IgM antibody titers remained stable from baseline up to day 140. - Interpretation - Vaccination with SUM-101 was safe and well-tolerated among adults living in a malaria-endemic region of Tanzania. Our findings justify further development of SUM-101 as component of next-generation subunit malaria vaccines. - Funding - Sumaya Biotech GmbH & Co. KG, Heidelberg, funded this study partly through support by a Venture Loan Agreement to Sumaya Biotech GmbH & Co. KG by the EU Malaria Fund Berlin GmbH & Co. KG.
Gesehen am 17.02.2026
Online veröffentlicht: 25. Oktober 2025